Oxidative Stability of the Meat of Broilers Fed Diets Supplemented with Various Levels of Blackcurrant Extract (Ribes nigrum L.) during Different Time Period - Kamil Sierżant; Małgorzata Korzeniowska; Barbara Król; Janusz Orda; Aneta Wojdyło (Journal of Chemistry)
In the 20 d experiment, the influence of different concentration and supplementation period of commercial blackcurrant extract (BC) in the broiler diets on the oxidative stability of breast and thigh meat, as well as selected performance indices, was investigated. A number of 120 fifteen-d-old Hubbard Flex male chicks (initial BW 363.5 ± 22.9 g) were randomly allocated to five groups: the control and four treatments (6 replicates, 4 birds per cage in each group). The BC extract was administrated to treatment groups at two concentrations (1.25 and 2.5 g/kg) and in different periods within the trial (i.e., from 15 to 35 d and from 25 to 35 d of life). Body weight gain (BWG) and feed conversion ratio (FCR) were determined during the 20-d experiment. At d 35, two randomly selected birds from each cage were decapitated, and pectoral and thigh muscles were collected. Extent of lipid oxidation after storage at chilling (2-3°C, 1, and 5 d) and freezing conditions (after 90 d, −18°C) was determined. The chickens’ growth performance and FCR were not affected by the concentrations and periods of BC supplementation. The enrichment of grower diet with 1.25 g/kg of BC extract reduced the malondialdehyde (MDA) formation in frozen thigh muscles (P<0.05), and this effect tended to appear (P<0.089) irrespective of duration of the supplementation period. Significant extent of lipid oxidation process was found in 1-d-chilled pectoral muscles of chickens receiving BC diet for 20 d or diet containing 2.5 g/kg of the extract. The results showed that BC extract may be an efficient source of antioxidants in chicken diet, which may increase oxidative stability of frozen dark meat. However, the conditions and ability of some polyphenols to initiate oxidation processes have not been fully understood and further studies are required.